Underestimated Cervical Extradural Hematoma Secondary to the Small Needle-Scalpel for the Treatment of Cervical Spondylosis: A Rare but Avoidable Complication - Han, Jinming; Yang, Meng-ge; Zhang, Qingxiang; Jin, Tao (Frontiers in Neurology, 2019)
Objective: To present a case report highlighting a severe, yet avoidable, complication following small needle-scalpel treatment for cervical spondylosis. Introduction: The small needle-scalpel is a miniature surgical instrument used to create intense and invasive punctures at certain acupoints with a small latch needle. It has been increasingly gaining popularity among clinicians and patients all over the world during the past years. However, severe complications after small needle-scalpel treatment have not previously been reported. Methods: Here we report a 54-year-old man who recently suffered from cervical spondylosis and underwent small needle-scalpel treatment, which was performed by a rural doctor. While there were no new neurologic deficits, the patient experienced delayed functional deterioration until the onset of quadriplegia within one month of treatment. Magnetic resonance imaging demonstrated a C2–C7 dorsally placed extradural hematoma with severe cord compression and subcutaneous soft tissue hemorrhage. Results: The patient refused urgent corrective surgery and later died due to respiratory failure. Conclusions: Although small needle-scalpel therapy has many benefits, such as reducing pain, shorter expenditure, shorter period of therapy and better recovery of function, there are also many potentially severe risks, such as cervical extradural bleeding, which requires clinicians to pay more attention to avoid the complications.